Asian Option Pricing with Monotonous Transaction Costs under Fractional Brownian Motion - Di Pan; Shengwu Zhou; Yan Zhang; Miao Han (Journal of Applied Mathematics)
Geometric-average Asian option pricing model with monotonous transaction cost rate under fractional Brownian motion was established. The method of partial differential equations was used to solve this model and the analytical expressions of the Asian option value were obtained. The numerical experiments show that Hurst exponent of the fractional Brownian motion and transaction cost rate have a significant impact on the option value.